2015
DOI: 10.1371/journal.pone.0120559
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Antidepressants “Fluoxetine and Imipramine” on Vascular Abnormalities and Toll Like Receptor-4 Expression in Diabetic and Non-Diabetic Rats Exposed to Chronic Stress

Abstract: Several studies reveal that diabetes doubles the odds of comorbid depression with evidence of a pro-inflammatory state underlying its vascular complications. Indeed, little information is available about vascular effects of antidepressant drugs in diabetes. Method: We investigated the effect of chronic administration of fluoxetine “FLU” and imipramine “IMIP” on behavioral, metabolic and vascular abnormalities in diabetic and non-diabetic rats exposed to chronic restraint stress (CRS). Results: Both diabetes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 69 publications
4
26
1
Order By: Relevance
“…The results of this work alongside our previously published work [16] showed that the metabolic abnormalities induced by type 2 DM were more prominent with CRS accompanied by decreased body weight gain and increased serum corticosterone levels which indicate the absence of adaptive response to stress. Chronic treatment with FLU and IMIP reversed these changes in a comparable manner.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The results of this work alongside our previously published work [16] showed that the metabolic abnormalities induced by type 2 DM were more prominent with CRS accompanied by decreased body weight gain and increased serum corticosterone levels which indicate the absence of adaptive response to stress. Chronic treatment with FLU and IMIP reversed these changes in a comparable manner.…”
Section: Discussionsupporting
confidence: 65%
“…In a previous work, we have concluded that TLR-4 and subsequent cytokine production may underlie diabetes and psychological stress associated vascular complications [16]. The results of this work emphasize that TLR-4 activation not only underlies complications but it may be also involved in the pathogenesis of both depression and DM.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Fluoxetine is a widely used antidepressant which could reverse depressive-like and anxiety-like behaviors (Habib, Shaker, El-Gayar, & Aboul-Fotouh, 2015;Lehmann et al, 2013;Wang et al, 2014). But there is limited evidence about whether TLR4 is involved in the antidepressant effect of fluoxetine.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that TLR expression is elevated in muscles, adipocytes, and B lymphocytes in DM patients. Further genetic studies in Chinese type II DM patients have revealed a correlation between polymorphisms in the TLR-4 gene and disease progression, suggesting the involvement of TLR-2 and TLR-4 in the mediation of both type I and type II DM (Habib et al, 2015;Singh et al, 2015a,b). The function of these two factors in DR and the related mechanism, however, remains unclear.…”
Section: Introductionmentioning
confidence: 99%